IMPLEMENTASI TEKNIK SINEMATOGRAFI DALAM PROSES PRODUKSI VIDEO IKLAN DI AGRO EDUWISATA ORGANIK MULYAHARJA: The Implementation of Cinematography Techniques in Advertising Production Process at Mulyaharja Organic Agro Edutourism - Dwikurnia, Muhammad Rifqi; Pambudy, Rachmat; Ulya, Enden Darjatul (Universitas Trisakti, 2024)
The Implementation of Cinematography Techniques in Advertising Production Process at Mulyaharja Organic Agro Edutourism. Mulyaharja Organic Agro Edutourism is a tourist village location that uses rice fields as educational and tourism material for the community. Mulyaharja Organic Agro Edutourism uses social media Instagram to convey information for its various services. Interesting content is needed so that the information conveyed via Instagram social media can be conveyed according to the intended target. This final project focuses on the role of a videographer and the production of advertising videos with the implementation of cinematography techniques. This advertising video production stage applies various cinematographic techniques, namely the type of shooting, shooting angles, composition, and camera movement. This advertising video lasts 4 minutes 36 seconds with a ratio of 9:16 in MP4 format, aiming to be a social media advertisement for the Mulyaharja Organic Agro Eduwisata Instagram social media.